Pertanggung Jawaban Hukum Bagi Pelaku Konsumsi Miras Di Kecamatan Mojolaban - Laksono, Hanafi Dwi Laksono; Laksono, Hanafi Dwi (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
The behavior of consuming alcohol in the Sukoharjo district, Central Java province has made the environment around the community become disturbed and uncomfortable, this behavior can be included in the category of social pathology, so that the authorities or in this case the police give punishment to the perpetrator for this detrimental action in order to reduce negative impact on the community environment and in order to minimize the spread of alcohol consumption behavior. People who consume alcohol usually start drinking around 10 pm to 3 am, sometimes people who consume alcohol also make noise on the street and even around people's homes. The aim of this research is to provide education to the wider community regarding law enforcement regarding alcohol consumption activities. This research method uses normative legal research methods using qualitative data analysis. The results of this research show that the perpetrators of alcohol consumption consist of various age groups between 18 years and 50 years, however, the majority of those who consume alcohol are young people aged 18 to 25 years. This condition occurs because young people lack knowledge about the dangers of consuming alcohol and what legal consequences result from consuming alcohol. Cultural factors and the social environment are also the causes of alcohol consumption behavior.